Arsenic-Induced Keratosis and Bowen's Disease (Medicine Today, 2026)
Introduction with objective: Arsenicosis is a major public health problem in Bangladesh. The most common manifestation of arsenicosis is the development of keratosis in the palms and soles which affect the economic condition of the patients by reducing their working ability. In addition, it may cause Bowen’s disease. The aim of the present study was to observe the keratoses and Bowens disease patients due to arsenicosis. Materials and Methods: This Observational study was carried out among 31 arsenic induced Bowen’s disease and keratoses patients at the Pharmacology department, Bangladesh Medical University (BMU), Dhaka and two arsenic affected endemic areas [Bhanga Upazilla of Faridpur District (about 150 km from Dhaka) and Babutipara Union, Muradnagar Upazilla, Cumilla District (about 108 km from Dhaka)] from September 2017 to January 2019. Purposive sampling was done according to availability of the patients. All the data were compiled and sorted properly and the quantitative data was analyzed statistically by using Statistical Package for Social Science. Result: The mean (± SD) age of the arsenical keratosis patients was 41.3 ± 13 years. The mean amount of arsenic in the tube well water consumed by the arsenical keratosis patients was 222.4 ± 111.3 μg/L and in the nail sample of the patients was 8.8 ± 4.3 μg/g. The mean duration of exposure to arsenic contaminated water of the arsenical keratosis patients was 11.3 ± 1.7 years. The mean duration of the appearance of arsenical keratosis lesions was 6.5 ± 2.1 years. The mean (± SD) age of the Bowen's patients was 56.2 ± 4.4 years. The mean amount of arsenic in the tube well water consumed by the Bowen's patients was 222.4 ± 111.3 μg/L and in the nail sample of the Bowen's patients was 8.8 ± 4.3 μg/g. The mean duration of exposure to arsenic contaminated water of the Bowen's patients was 11.3 ± 1.7 years. The mean duration of the appearance of lesions was 6.5 ± 2.1 years. Conclusion: Chronic arsenicism may lead to both cutaneous and systemic neoplasms and patients should undergo regular long-term examination.Medicine Today 2026, Vol.38 (1): 96-98